2016
DOI: 10.1021/acs.nanolett.6b01946
|View full text |Cite
|
Sign up to set email alerts
|

Diode-Pumped Organo-Lead Halide Perovskite Lasing in a Metal-Clad Distributed Feedback Resonator

Abstract: Organic-inorganic lead halide perovskite semiconductors have recently reignited the prospect of a tunable, solution-processed diode laser, which has the potential to impact a wide range of optoelectronic applications. Here, we demonstrate a metal-clad, second-order distributed feedback methylammonium lead iodide perovskite laser that marks a significant step toward this goal. Optically pumping this device with an InGaN diode laser at low temperature, we achieve lasing above a threshold pump intensity of 5 kW/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
248
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(256 citation statements)
references
References 56 publications
6
248
2
Order By: Relevance
“…Recently, organic-inorganic metal halide perovskites have attracted much interest from the scientific community for various applications, including solar cells, [1][2][3][4][5][6][7][8][9][10][11][12] lasers, [13][14][15] light emitting diodes (LED), [16][17][18] water splitting, [19,20] photodetectors, [21][22][23][24][25] field-effect transistors, [26][27][28][29][30] nonvolatile memory, [31,32] capacitors, [33] battery, [34,35] optical amplifiers, [36] lasing, [37][38][39] and laser cooling. [40] They are now considered the most exceptional materials due to their high efficiency and ease in fabrication, and the materials used to form perovskite are extensively available and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic-inorganic metal halide perovskites have attracted much interest from the scientific community for various applications, including solar cells, [1][2][3][4][5][6][7][8][9][10][11][12] lasers, [13][14][15] light emitting diodes (LED), [16][17][18] water splitting, [19,20] photodetectors, [21][22][23][24][25] field-effect transistors, [26][27][28][29][30] nonvolatile memory, [31,32] capacitors, [33] battery, [34,35] optical amplifiers, [36] lasing, [37][38][39] and laser cooling. [40] They are now considered the most exceptional materials due to their high efficiency and ease in fabrication, and the materials used to form perovskite are extensively available and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the following work on perovskite thin films concentrated on the workhorse composition for solar cells, methylammonium (CH 3 NH 3 /MA) lead (Pb) triiodide (I 3 ) that emits around 790 nm. Random lasers [18], whispering gallery mode lasers [19][20][21][22], distributed feedback lasers [23][24][25], vertical cavity lasers [26,27] and photonic crystals lasers have been demonstrated using this CH 3 NH 3 PbI 3 composition [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of triiodide perovskites was shown to be excellent [17,23], although hurdles still remain to achieving continuous-wave lasing [24,30]. Photophysical investigations of CH 3 NH 3 PbX 3 with mixed-halides undertaken in the context of bandgap tuning for photovoltaics revealed that the emission wavelength and intensity of the mixed-halide material is highly unstable under illumination [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…An optically pumped NIR perovskite laser using longer pulses (nanoseconds) was recently demonstrated [26], but it was operated in a cryogenic environment. A similar attempt was also reported for an NIR perovskite VCSEL [27].…”
mentioning
confidence: 99%
“…Nevertheless, a first enhanced ASE for a perovskite device is obtained here under CW pumping. Several attempts for perovskite lasing [24,26,27] and ASE [12,33,34] under longer pulse (nanosecond) pumping were reported recently to understand the challenges that hinder CW optical pumping. Among the challenges to be overcome are Auger recombination, material quality, and thermal stability [6][7][8]27,34].…”
mentioning
confidence: 99%